Effect Of Kenikir Leaves Extract On Gastric Histology Description Of Male White Rats Induced By Aspirin - Nurri Yusriyyah JS; Husnarika Febriani; Syukriah syukriah (Al-Hayat: Journal of Biology and Applied Biology, 2022)
Using aspirin for long time make ulcer. Using traditional medicinal plants is alternative in treating gastric ulcers. This experiment aims to determine effect of kenikir leaves extract (Cosmos caudatus Kunth.) on gastric morphology and histology decription of male white rats (Rattus norvegicus) induced by aspirin. 25 rats were divided into 5 groups, KN (control), KP (aspirin 200 mg/kgBW for 10 days), P1 (aspirin 200 mg/kgBW for 10 days + kenikir leaves extract 700 mg/kgBW for 14 days). ), P2 (aspirin 200 mg/kgBW for 10 days + kenikir leaves extract 800 mg/kgBW for 14 days), P3(aspirin 200 mg/kgBW for 10 days+kenikir leaves extract 900 mg/kgBW for 14 days). Parameters observed were morphological and histological of the gastric. Data were analyzed by oneway ANOVA test and continued with Duncan's test. The results kenikir leaves did not have a significant effect on the morphology but histologically, kenikir leaves extract had a significant effect by improving the thickness of gastric layer. It can be concluded that kenikir leaves extract can be used as an alternative to treat gastric ulcers because it can improve the thickness of gastric layer.